Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the given system of equations by elimination, follow these steps:
Given system of equations:
[tex]\[ \begin{cases} 3a + 6b = 12 \quad \text{(Equation 1)} \\ -3a + 6b = -12 \quad \text{(Equation 2)} \end{cases} \][/tex]
### Step 1: Eliminate variable [tex]\(a\)[/tex]
Add Equation 1 and Equation 2 to eliminate [tex]\(a\)[/tex]:
[tex]\[ (3a + 6b) + (-3a + 6b) = 12 + (-12) \][/tex]
Combine like terms:
[tex]\[ 3a - 3a + 6b + 6b = 0 \][/tex]
Simplify:
[tex]\[ 0a + 12b = 0 \quad \Rightarrow \quad 12b = 0 \quad \text{(Resulting Equation 1)} \][/tex]
### Step 2: Eliminate variable [tex]\(b\)[/tex]
Subtract Equation 2 from Equation 1 to eliminate [tex]\(b\)[/tex]:
[tex]\[ (3a + 6b) - (-3a + 6b) = 12 - (-12) \][/tex]
Combine like terms:
[tex]\[ 3a + 3a + 6b - 6b = 24 \][/tex]
Simplify:
[tex]\[ 6a + 0b = 24 \quad \Rightarrow \quad 6a = 24 \quad \Rightarrow \quad a = 4 \quad \text{(However, we will keep it as \(6a = 24\) for consistency)} \][/tex]
### Conclusion:
The possible resulting equations from eliminating one of the variables can be:
1. [tex]\(12b = 0\)[/tex]
2. [tex]\(6a = 0\)[/tex]
From the given options, the correct resulting equations are:
[tex]\[ \boxed{12b = 0 \quad \text{and} \quad 6a = 0} \][/tex]
Given system of equations:
[tex]\[ \begin{cases} 3a + 6b = 12 \quad \text{(Equation 1)} \\ -3a + 6b = -12 \quad \text{(Equation 2)} \end{cases} \][/tex]
### Step 1: Eliminate variable [tex]\(a\)[/tex]
Add Equation 1 and Equation 2 to eliminate [tex]\(a\)[/tex]:
[tex]\[ (3a + 6b) + (-3a + 6b) = 12 + (-12) \][/tex]
Combine like terms:
[tex]\[ 3a - 3a + 6b + 6b = 0 \][/tex]
Simplify:
[tex]\[ 0a + 12b = 0 \quad \Rightarrow \quad 12b = 0 \quad \text{(Resulting Equation 1)} \][/tex]
### Step 2: Eliminate variable [tex]\(b\)[/tex]
Subtract Equation 2 from Equation 1 to eliminate [tex]\(b\)[/tex]:
[tex]\[ (3a + 6b) - (-3a + 6b) = 12 - (-12) \][/tex]
Combine like terms:
[tex]\[ 3a + 3a + 6b - 6b = 24 \][/tex]
Simplify:
[tex]\[ 6a + 0b = 24 \quad \Rightarrow \quad 6a = 24 \quad \Rightarrow \quad a = 4 \quad \text{(However, we will keep it as \(6a = 24\) for consistency)} \][/tex]
### Conclusion:
The possible resulting equations from eliminating one of the variables can be:
1. [tex]\(12b = 0\)[/tex]
2. [tex]\(6a = 0\)[/tex]
From the given options, the correct resulting equations are:
[tex]\[ \boxed{12b = 0 \quad \text{and} \quad 6a = 0} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.